Community health workers’ quality of comprehensive care: a cross-sectional observational study across three districts in South Africa - Babalola, Olukemi; Levin, Jonathan; Goudge, Jane; Griffiths, Frances (Frontiers in Public Health, 2023)
Background Community healthcare worker (CHW) training programs are becoming increasingly comprehensive (an expanded range of diseases). However, the CHWs that the program relies on have limited training. Since CHWs’ activities occur largely during household visits, which often go unsupervised and unassessed, long-term, ongoing assessment is needed to identify gaps in CHW competency, and improve any such gaps. We observed CHWs during household visits and gave scores according to the proportion of health messages/activities provided for the health conditions encountered in households. We aimed to determine (1) messages/activities scores derived from the proportion of health messages given in the households by CHWs who provide comprehensive care in South Africa, and (2) the associated factors. Methods In three districts (from two provinces), we trained five fieldworkers to score the messages provided by, and activities of, 34 CHWs that we randomly selected during 376 household visits in 2018 and 2020 using a cross-sectional study designs. Multilevel models were fitted to identify factors associated with the messages/activities scores, adjusted for the clustering of observations within CHWs. The models were adjusted for fieldworkers and study facilities (n = 5, respectively) as fixed effects. CHW-related (age, education level, and phase of CHW training attended/passed) and household-related factors (household size [number of persons per household], number of conditions per household, and number of persons with a condition [hypertension, diabetes, HIV, tuberculosis TB, and cough]) were investigated. Results In the final model, messages/activities scores increased with each extra 5-min increase in visit duration. Messages/activities scores were lower for households with either children/babies, hypertension, diabetes, a large household size, numerous household conditions, and members with either TB or cough. Increasing household size and number of conditions, also lower the score. The messages/activities scores were not associated with any CHW characteristics, including education and training. Conclusion This study identifies important factors related to the messages provided by and the activities of CHWs across CHW teams. Increasing efforts are needed to ensure that CHWs who provide comprehensive care are supported given the wider range of conditions for which they provide messages/activities, especially in households with hypertension, diabetes, TB/cough, and children or babies.